2010
DOI: 10.1002/ajh.21883
|View full text |Cite
|
Sign up to set email alerts
|

Examining the characteristics and beliefs of hydroxyurea users and nonusers among adults with sickle cell disease

Abstract: The attitudes of patients with sickle cell disease (SCD) toward the use of hydroxyurea (HU) therapy may contribute to the underutilization of HU in the United States, yet our understanding of these attitudes is limited. We examined the attitudes and beliefs of 94 adult SCD patients, comparing those who never used HU (n = 37), formerly used HU (n = 23), and were currently using HU (n = 34). Seventy percent of current HU users reported some level of improvement from the drug (“average” or “very much”) and 80% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 20 publications
4
64
2
Order By: Relevance
“…A recent meta-analysis reported lower adherence rates in older patients and those with more identified barriers [16], which are numerous and varied in the literature [1322]. Nevertheless, the relationship between patients’ perceptions of both hydroxyurea and SCD and their adherence to hydroxyurea has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis reported lower adherence rates in older patients and those with more identified barriers [16], which are numerous and varied in the literature [1322]. Nevertheless, the relationship between patients’ perceptions of both hydroxyurea and SCD and their adherence to hydroxyurea has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Insights from prior research in other health conditions suggest barriers to medication use among chronically ill under-served populations generally involve provider-patient relationship dynamics [1618]. Additional barriers to medication use include incomplete knowledge of drug benefit and logistical factors that impede access to care [19–21]. As a chemotherapeutic agent, barriers to off-label HU therapy likely also include concerns about the safety of short- and long-term use [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additional barriers to medication use include incomplete knowledge of drug benefit and logistical factors that impede access to care [19–21]. As a chemotherapeutic agent, barriers to off-label HU therapy likely also include concerns about the safety of short- and long-term use [21]. While providers have been surveyed about their perceived barriers to HU therapy [15,22–25], no studies on barriers to HU among parents of children with SCD have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that HC increases survival in SCA (Steinberg et al, 2010;Voskaridou et al, 2010;Lobo et al, 2013), and its use is being recommended to a growing number of SCA patients, including children (McGann & Ware, 2011), In practice, however, many eligible patients are not taking the drug (Rees, 2011). One reason for this is the perception that HC could be carcinogenic (Zumberg et al, 2005;Haywood et al, 2011). Although therapy-related acute myeloid leukaemia (t-AML) has been associated with a number of chaemotherapeutic agents, HC has not been shown to be leukaemogenic.…”
mentioning
confidence: 99%